Factors Causing Panic Purchasing Behavior in the COVID-19 Pandemic and Customer Satisfaction With Government Intervention as Moderating Variable - Qibtiyah, Desy Bariyyatul; Dharmmesta, Basu Swastha (Gadjah Mada International Journal of Business, 2024)
The phenomenon of panic buying is essential to observe during the pandemic of COVID-19. Additionally, research on panic buying spans multiple studies fields and deserves more consistent scientific attention. This study examines the factors of panic buying behavior using the Theory of Maslow's Hierarchy of Needs to scrutinize panic buying behavior regarding consumer needs. Subsequently, this study investigates the moderating variables of government intervention to fill the research gap. Furthermore, this study looks for the effect that resulted from the phenomenon of panic buying behavior on customer satisfaction. The data were collected from 456 grocery and drug store consumers in Indonesia who shopped throughout the pandemic of COVID-19. The PLS-SEM was used to analyze the data. The outcomes indicate that control, social media, perceived severity, and perceived scarcity significantly affect panic buying behavior. In contrast, the government intervention only moderated the effect of social media on panic buying. Finally, the phenomenon of panic buying significantly affects customer satisfaction.